Head first Java - Sierra, Kathy; Bates, Bert (Head first series., 2005)
Learning a complex new language is no easy task, especially when it's an object-oriented computer programming language like Java. Your brain doesn't always want to take in the dry, technical stuff you're forced to study. Your brain craves novelty. Head First Java combines puzzles, strong visuals, mysteries, and soul-searching interviews with famous Java objects to engage you in many different ways. Despite its playful appearance, Head First Java is serious: a complete introduction to object-oriented programming and Java. Its unique approach not only shows you what you need to know about Java syntax, it teaches you to think like a Java programmer. You'll learn everything from the fundamentals to advanced topics, including threads, network sockets, and distributed programming with RMI. The second edition focuses on Java 5.0, a major update to the platform, with deep, code-level changes--From publisher description.